Penerapan Teknologi Smart Greenhouse Berbasis Photovoltaic dan IoT pada Budidaya Sayuran Hidroponik di Desa Pekalongan Jepara - Andi Riansyah; Muhammad Sagaf; Munaf Ismail (Abdimas Universal, 2023)
Hydrofarm farming has problems when the electricity goes out causing the flow of nutrients to the plants to not be able to flow because the pump is off because it only uses electricity from PLN. If this continues, it can cause the plant to die because it is not supplied with nutrients. Apart from that, there are still other disadvantages if you provide nutrition using the manual method. The solution to this partner's problem was provided by the UNISSULA community service team by implementing photo voltaic technology in the Solar Power Plant (PLTS) system as a source of electricity to replace PLN electricity voltage. The use of internet technology is also applied to marketing partners for hydrofarm agricultural products. The results of using PLTS in hydrofarm agricultural operations can replace PLN electricity for 4 hours per day so that it can increase hydrofarm operational efficiency. Online marketing can also expand the marketing of hydrofarm agricultural products from partners so that the marketing area is wider.